Lebe Bae Baku Sayang: Moderasi Beragama ala Pemuda Lintas Iman di Kelurahan Honipopu Kota Ambon - Anwar, Ahsani Amalia; Rahayaan, Vitalia; Titawael, Ekmon (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the strategic role of interfaith youth in Honipopu Subdistrict, Ambon City, in preserving and promoting the local wisdom of lebe bae baku sayang as a strategy for strengthening religious moderation amidst the challenges of pluralism and a history of socio-religious conflict. Employing a qualitative approach with a case study design, the research draws on in-depth interviews, participant observation, and documentation from the interfaith youth community as primary data sources. The findings reveal that the value of lebe bae baku sayang, which means